2014
DOI: 10.1007/s11427-014-4650-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and regulatory network analysis of survival-related genes of patients with colorectal cancer

Abstract: The purpose of this study was to screen key survival-related genes from patients with colorectal cancer and explore signal transduction network of the involved genes. In a previous study, survival-related genes of patients with colorectal cancer were selected by colorectal cancer-related expression data GSE17538 using the Significance Analysis of Microarrays (SAM3.01) software, and 235 genes related to the survival of patients with colorectal cancer were obtained. Therefore, the following screening and analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…NF-κB signaling pathway hyperactivation plays critical roles in different malignant progression-associated processes, including tumorigenesis, angiogenesis, invasion, and metastasis 12 – 16 . Our previous bioinformatics analysis of several public gene expression profiles showed that STX2 upregulation was correlated with a poor prognosis for CRC patients and could increase the activity of the NF-κB signaling pathway 17 . However, the molecular mechanisms through which STX2 regulates NF-κB signaling pathway activation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB signaling pathway hyperactivation plays critical roles in different malignant progression-associated processes, including tumorigenesis, angiogenesis, invasion, and metastasis 12 – 16 . Our previous bioinformatics analysis of several public gene expression profiles showed that STX2 upregulation was correlated with a poor prognosis for CRC patients and could increase the activity of the NF-κB signaling pathway 17 . However, the molecular mechanisms through which STX2 regulates NF-κB signaling pathway activation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…KLK6 mRNA expression is elevated in malignant colorectal tissues compared with non-malignant ones and correlates with serosal invasion, liver metastasis, advanced Duke's stage, and a poor prognosis [17], [18], [19]. The bioinformatics analysis of expression data from a cohort of colorectal cancer patients, identified the KLK6 gene as one of the top six up-regulated genes associated with the survival of colorectal cancer patients through metastasis related signaling pathways [20]. The mechanism of regulation of KLK6 expression in colon cancer is not fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effect of the gene is not affected by lifestyle. CREB5 gene affects the survival of patients by regulating colorectal cancer metastasis-associated signaling pathways [31]. Moreover, the additive effect of another gene LMNTD1 also did not significantly changed in the cofactor models.…”
Section: Plos Onementioning
confidence: 86%